Long pentraxin 3 and vitamin D receptor mRNA expression pattern of cumulus granulosa cells isolated from PCOS oocytes at different stages of nuclear maturation - Ersahin, Aynur; Celik, Onder; Gungor, Nur D.; Celik, Nilufer; Melil, Sureyya; Yardim, Meltem; Akkoc, Ramazan F. (Bmc, 2024)
BackgroundA fine-tuned pro-inflammatory and anti-inflammatory balance in the follicular unit is essential for cumulus expansion and successful ovulation. While the long pentraxin 3 (PTX3) gene is required for the expansion of cumulus cells (CCs), ovulation, resumption of meiosis and fertilization, the vitamin D receptor gene (VDR-X2) is required for intra-follicle redox balance. This study was planned to determine the expression pattern of VDR-X2 and PTX3 mRNA in CCs isolated from germinal vesicle (GV), metaphase I (MI), and metaphase II (MII) oocytes of PCOS patients with ovulatory dysfunction.MethodsThe relative expression of CC-PTX3 and CC-VDR-X2 mRNA were evaluated using qRT-PCR in a total of 79 CC samples collected from individual cumulus-oocyte complex of 40 infertile patients (20 PCOS and 20 non-PCOS normal responders) who underwent ovarian stimulation with the GnRH antagonist protocol.ResultsRelative PTX3 mRNA expressions of CCMI-control and CCMII-control showed 3- and 9-fold significant upregulation compared to CCGV-control, respectively. The relative PTX3 mRNA expression of CCMII-control increased approximately three fold compared to CCMI-control. Compared to CCGV-pcos, a 3-fold increase was noted in the relative PTX3 mRNA expression of CCMI-pcos and an approximately 4-fold increase in the PTX3 mRNA expression of CCMII-pcos. Relative PTX3 mRNA expression values of CCMII-pcos and CCMI-pcos were similar. A 6-fold upregulation of relative PTX3 mRNA and a 4-fold upregulation of VDR-X2 mRNA were detected in CCMII-control compared to CCMII-pcos. CC-VDR-X2 expression patterns of the PCOS and control groups overlapped with the CC-PTX3 pattern. Fertilization rates of the PCOS group exhibiting failed transcript expression were similar to normal responders.ConclusionThe fact that relative CC-PTX3 and CC-VDR mRNA expression does not increase during the transition from MI to MII stage in PCOS as in normal responders suggests that PTX3 and VDR expression may be defective in cumulus cells of PCOS patients with ovulatory dysfunction.
Keywords: Polycystic ovary syndrome; Cumulus expansion; VDR, PTX3, fertilization